2018
DOI: 10.1037/xap0000162
|View full text |Cite
|
Sign up to set email alerts
|

Self-persuasion in media messages: Reducing alcohol consumption among students with open-ended questions.

Abstract: Self-persuasion (self-generation of arguments) is often a more effective influence technique than direct persuasion (providing arguments). However, the application of this technique in health media communications has received limited attention. In two experiments, it was examined whether self-persuasion can be successfully applied to antialcohol media communications by framing the message as an open-ended question. In Experiment 1 (N = 131) cognitive reactions to antialcohol posters framed either as open-ended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 49 publications
3
52
0
1
Order By: Relevance
“…Each label was displayed for 15 seconds. Direct persuasion labels were formulated as statements and self-persuasion labels were formulated as questions (see Glock et al, 2013;Loman et al, 2018;Müller et al, 2016). Health-related label content or POErelated label content was emphasized in both statements and questions (all labels can be found in the Replication package).…”
Section: Methodsmentioning
confidence: 99%
“…Each label was displayed for 15 seconds. Direct persuasion labels were formulated as statements and self-persuasion labels were formulated as questions (see Glock et al, 2013;Loman et al, 2018;Müller et al, 2016). Health-related label content or POErelated label content was emphasized in both statements and questions (all labels can be found in the Replication package).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, self-persuasion may increase perceived severity and vulnerability to COVID-19 as a result of convincing oneself to socially isolate during the COVID-19 pandemic. This line of reasoning is supported by a study, which showed that self-persuasion is effective in increasing alcohol risk perception (Loman et al, 2018b), which is similar to the perceived threat of illness.…”
Section: Perceived Vulnerability and Severity Of Covid-19mentioning
confidence: 72%
“…Our results, combined with research showing that self-persuasion can be easily and effectively carried out through social media (Loman et al, 2018a) or by mobile application (Stavrositu & Kim, 2018), indicate potential opportunities for encouraging people to stay isolated during a pandemic. In order to apply self-persuasion there is no need to encourage people to create and write down their own arguments for social isolation, but it is enough to pose an open question (Loman, et al, 2018b) such as this in the media space: "Why is it worth limiting social contacts during the COVID pandemic?". Although the observed effect size is small, the application of persuasion on the scale of the whole population may significantly contribute to reducing the pandemic and may potentially save the lives of dozens of people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption behind this practice is that arguments would be automatically generated when people are exposed to open-ended questions. A recent study affirmed this assumption by exposing participants to anti-alcohol posters formulated either as an open-ended question or as a statement, and then asking them to list their thoughts during the exposure to the posters [25]. It was found that participants who were exposed to the question-formulated poster indeed reported pro-arguments in response to the question.…”
Section: Introductionmentioning
confidence: 94%